Covid-19, Family, and Information Literacy - Alim Harun Pamungkas; Wendi Ahmad Wahyudi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
Status of Specific Disasters Emergency Volume 1 and 2, Social distancing, physical distancing to Large Scale Social Restrictions (PSBB) is a series of policies adopted by the Government of Indonesia from the end of January to the end of March 2020 in response to the escalation the Covid-19 pandemic. However, the series of policies have not been able to reduce the number of positive victims of Covid-19. Since the first positive case of two people on March 2, 2020, the number of positive cases of Covid-19 has been increasing day by day. Data as of 30 April 2020 shows the number of 10,118 positive cases. The failure of the Indonesian Government's policy to suppress Covid-19's positive numbers, one of which is that there are still many Indonesians who do not heed the policies implemented by the government and the ineffective digital-based integrated information system that has been made by the government. One of these two factors, rooted in the ability of information literacy that is owned by the community, because the ability of information literacy will determine what people do in the midst of the Covid-19 pandemic. This paper tries to discuss how to build the ability of family-based information literacy so that the community has capital accumulated knowledge about the Covid-19 pandemic so that it can avoid the anxiety, fear, panic and pandemic Covid-19. Selected family-based because the PSBB policy implemented by the Indonesian Government emphasizes activities at home.Keywords: Covid-19, Family, Information Literacy